Intranasal oxytocin attenuates the effects of monetary feedback on procedural learning. (September 2022) - Doppler, Christopher E.J.; Meyer, Linda; Seger, Aline; Karges, Wolfram; Weiss, Peter H.; Fink, Gereon R.
Abstract: Procedural learning is a vital brain function that allows us to acquire motor skills during development or re-learn them after lesions affecting the motor system. Procedural learning can be improved by feedback of different valence, e.g., monetary or social, mediated by dopaminergic circuits. While processing motivationally relevant stimuli, dopamine interacts closely with oxytocin, whose effects on procedural learning, particularly feedback-based approaches, remain poorly understood. In a randomized, double-blind, placebo-controlled trial, we investigated whether oxytocin modulates the differential effects of monetary and social feedback on procedural learning. Sixty-one healthy male participants were randomized to receive a placebo or oxytocin intranasally. The participants then performed a modified serial reaction time task. Oxytocin plasma concentrations were measured before and after applying the placebo or verum. Groups did not differ regarding general reaction times or measures of procedural learning. For the placebo group, monetary feedback improved procedural learning compared to a neutral control condition. In contrast, the oxytocin group did not show a differential effect of monetary or social feedback despite a significant increase in oxytocin plasma levels after intranasal application. The data suggest that oxytocin does not influence procedural learning per se. Instead, oxytocin seems to attenuate the effects of monetary feedback on procedural learning specifically. Highlights: Monetary feedback improves procedural learning compared to a control condition. Procedural learning in general is not affected by oxytocin. Oxytocin does not enhance effects of social feedback on procedural learning. Effects of monetary feedback on procedural learning are attenuated by oxytocin.